The Impact of Human Resource Management Practices on Employee’ Commitment in Banking Sector in Malaysia - Zhou, Hui (2014)
Malaysia is experiencing fierce competition from the Asian/Pasific region, it is vital for companies in Malaysia to understand the fundamental drives influencing employees’ commitment to innovate successful new products, idea, practice and systems, only then can these companies compete successfully. As one of the twelve national key economic areas, the financial services sector, particularly the banking industry, has faced the problem of debacle, which would impacted greatly on internal and external customers’ confidence and perception over the years squarely on their management. This paper examined the impact of human resource management (HRM) practices’ (including orientation of recruits, formal operating guidelines, career planning and development) on employees’ commitment by descriptive analysis and correlation analysis based on validity test and reliability test, using survey data covering 300 employees (management, supervisors, administrators and clerks) from the banking sector (including Maybank, Hong leong Bank and RHB, 100 employees for each bank) in Selangor in the year of 2014. The significance of the study is to provide evidence to support the relationship (strategic fit) between HRM practices and employee commitment. The study also seeks to gain descriptive information on HRM policy and practices in the banking sector, together with an assessment of the organizational and environmental factors that drive HRM strategy and policy. The results can support for the design of high involvement work practices to foster organizational commitment and to improve long term organizational performance in developing economies. The findings also can contribute to an organization’s ability to understand the different components of commitment in order to experience overall efficiency and effectiveness from employees.